Mobile app for food give away - Soh, Bernard Ee Siang (Nanyang Technological University, 2022)
The aim of this project is to develop a simple and user-friendly platform using both front-end and back-end technologies to provide convenience to restaurant operators in the donation of untouched leftover food and soon-to-be expired ingredients. The project is constructed using Flutter as the main programming language to develop a mobile application. The app allows restaurant or shop owners to post pictures of food they want to give away, which other users can view on the app. If other users are interested in the items, they can communicate with the donor and set up a time and location to meet or collect. The increase in convenience encourages people to donate their food items or soon-to-be expired food which helps Singapore reduce one of its most significant waste sources; food waste. The system is built on Flutter, a portable Google User Interface (UI) toolkit for creating mobile or web applications which is commonly used in industry and popular for its ability for developing cross-platform applications by using a single codebase. Hence, there is potential to develop a web or desktop application from the mobile application developed for this project.